EVALUATING SCHOOL HEALTH PROGRAMME SUPPORT CAPACITY ACROSS EDUCATIONAL LEVELS IN GORONTALO CITY - RAMLY ABUDI; Susanti Iman (Jambura Journal of Health Sciences and Research, 2026)
The School Health Program (SHP) is a cross-sectoral initiative designed to promote healthy school environments and improve clean and healthy living behaviours among school-aged children. However, disparities in SHP implementation across regions have limited the effectiveness of the program, while previous studies have generally focused on specific educational levels, providing only a partial understanding of program support capacity. This study aimed to assess the support capacity of SHP implementation in public schools across Gorontalo City by evaluating human resources, management systems, and facilities and infrastructure. A quantitative descriptive study using a cross-sectional approach was conducted in 2017 involving 130 public schools, consisting of 107 elementary schools, 16 junior high schools, 3 senior high schools, and 4 vocational schools. Data were collected using questionnaires, observations, and interviews and analyzed descriptively using percentage distributions. The results showed that good human resource capacity was identified in 40.2% of elementary schools, 37.5% of junior high schools, and 28.6% of senior high and vocational schools. Good management systems were observed in 59.8%, 75.0%, and 85.7% of schools at the respective educational levels, while good facilities and infrastructure were reported in 52.3%, 56.3%, and 42.9% of schools. Overall, the SHP support capacity was categorized as good, although deficiencies remained in human resources and essential facilities. Strengthening the competencies of SHP management personnel through regular capacity-building programs is recommended to improve the quality and sustainability of healthy school implementation.